John R. Searle i ontologia prawa: [John R. Searle and ontology of law] (Studia Prawnicze / The Legal Studies, 2009)
Prawo jest elementem rzeczywistości społecznej. Ta zaś stała się w ostatnich dekadach przedmiotem intensywnych dociekań filozoficznych. Ich efekty pozwalają na to, aby w nowym świetle spojrzeć na wiele problemów doniosłych dla zrozumienia porządku prawnego i jego funkcjonowania Można nawet zaryzykować tezę, iż z prowadzonej od pewnego czasu dyskusji, której istotnym punktem jest ukazanie się „Konstrukcji rzeczywistości społecznej” Johna R. Searle’a zdają się wyłaniać zręby nowego paradygmatu filozoficznej refleksji nad społecznym poziomem rzeczywistości. W pracy tej Searle stara się w oparciu o wyniki swoich prowadzonych od lat 60-tych badań, w szczególności poświęconych funkcjonowaniu umysłu, świadomości i języka, ułożyć spójny obraz zależności pomiędzy światem obiektów fizycznych, reakcji chemicznych i procesów biologicznych, a światem zjawisk oraz faktów społecznych, kultury i wartości. An essay „John R. Searle and ontology of law” is devoted to a theory of social ontology being developed by one of the leading contemporary analytic philosophers. It is based on results achieved by cognitive science (of which Searle was one of co-founders) as well as his own earlier inquiries into language, speech acts and mind. This kind of project, the aim of which is to clarify a logical structure and mechanisms of constructing social reality, applying ideas of intentionality, status functions, constitutive rules and institutions unifies many various theories, findings and intuitions put forward in many fields of research including legal sciences. It enables us to identify and better understand not only common structure behind law and other social phenomena but also their relation to our conception of physical world as described by natural science. It seems that John Searle’s works contribute much to create a new paradigm of exploration and analysis of social world highly relevant for legal thinking. Furthermore, it sheds new light on many controversial problems and concepts of legal science. Despite the fact that the theory of social world as proposed by Searle is still at relatively early stage of development, its importance for understanding legal reality can hardly be overestimated.